Metallo supramolecular cylinders inhibit HIV-1 TAR-TAT complex formation and viral replication in cellulo - Cardo, L; Nawroth, I; Cail, P; McKeating, J; Hannon, M (Springer Nature, 2018)
Shape-selective recognition of nucleic acid structures by supramolecular drugs offers the potential to treat disease. The Trans Activation Response (TAR) region is a region of high secondary structure within the human immunodeficiency virus-1 (HIV-1) RNA that complexes with the virus-encoded Transactivator protein (TAT) and regulates viral transcription. Herein, we explore different metallo-supramolecular triple stranded helicates (cylinders) that target the TAR bulge motif and inhibit the formation of TAR-TAT complexes and HIV infection. Cylinders that incorporate Ni(II) and Ru(II) showed the most potent anti-viral activity with limited evidence of cellular cytotoxicity. These metallo-supramolecular compounds provide an exciting avenue for developing a new class of anti-viral agents.